Comparison of Standard, Fluorogenic and Chromogenic Substrate Based Methods for Enumeration of Escherichia coli in Sasthamkotta Lake of Kerala, India - Visnuvinayagam, Sivam; Murugadas V.; Manasa Das; Nair V., Radhakrishnan; Sivaraman G. K.; Toms C. Joseph (Fishery Technology, 2023)
Discovery of chromogenic and fluorogenic substances has made the conventional method more hassle-free to detect specific bacteria. A comparative analysis was conducted to assess the effectiveness of fluorogenic and chromogenic substrates in aiding the enumeration of E. coli of Sasthamkotta Lake located in Kerala, India. The fluorogenic compound, 4-Methyl umbelliferyl-D-glucuronide (MUG) is employed for the detection of E. coli in food and water. Similarly, a chromogenic substance, viz., 5- Bromo-4-chloro-3-indolyl-ß glucuronic acid (BCIG) is also employed for E. coli identification in food in ISO 16649-3. The present study compared the fluorogenic and chromogenic techniques with the standard method for enumerating E. coli by the most probable number (MPN) method. To enumerate the E. coli, a total of sixteen water samples were collected from Sasthamkotta Lake of Kerala, India and analyzed by 5-tube MPN method. Quantitatively, the results showed that, chromogenic approach revealed the highest E. coli count, followed by the fluorogenic and standard methods. Qualitatively, among the 16 samples, 11 samples were positive in standard method whereas for other methods, all 16 samples were positive. Hence it can be concluded that, in traditional enumeration technique, there is a substantial chance of under representation of E. coli by this method. On the other hand, there is chance of over-representation of E. coli in the chromogenic and fluorogenic aided methods. Based on the study, it is suggested that a combination of fluorogenic and chromogenic methods, i.e., EC-MUG followed by BCIG plating, would reduce the false positive or reduce the over representation of E. coli enumeration.